Preliminary Environmental Impact Assessment for the Geothermal Field Chachimbiro in Ecuador. A Case Comparison with Bjarnarflag Geothermal Field in Iceland - Rodas, Mario A., 1979- (2010)
The Chachimbiro geothermal area is located on the eastern flank of the Los Andes Western Mountain Range, in the province of Ibarra in Ecuador. This area is one of the many areas that had been investigated for the use of the geothermal steam, since Ecuador is the country with the most geothermal capacity among the countries that have not yet developed this energy. This study tries to determine the possible impacts of the exploration and production of this geothermal field and the implications that these activities will have on the environment and the people living near the area or site of interest. The goal of this study is to create a Preliminary Environmental Impact Assessment document which identifies the key possible environmental and social impacts associated with the development of the geothermal field in Chachimbiro (Ecuador). The research work consisted of a literature review, observing the similarities with comparable projects in Iceland (geothermal field Bjarnarflag in Iceland) and other countries in order to find the most common and possible impacts. Leading experts in the geothermal field in Iceland, including chemists, geologists and experts on environmental impact assessments were consulted concerning the possible effects of a geothermal development in the area, according to their experience. Most of the literature and also the Icelandic experts agreed on the impacts during all phases of geothermal development, this gives an idea that effects of geothermal development over the environment and society are more or less similar all over the world with some differences, especially according to the chemical composition of the geothermal fluid and also there could be differences in the magnitude and significance of the impacts according to the location of the fields. National Secretariat of Science and Technology of Ecuador (SENACYT)